Rhabdomyosarcoma Arising in a Giant Congenital Melanocytic Nevus. Issue 5 (9th June 2014) - Christman, Mitalee P.; Kerner, Jennifer K.; Cheng, Carol; Piris, Adriano; Nepo, Anne G.; Sepehr, Alireza; Kroshinsky, Daniela
Abstract A number of lesions have been documented to arise within congenital melanocytic nevi (CMNs). Although the most frequent malignancy arising within a CMN is melanoma, the association between rhabdomyosarcoma and CMN has rarely been documented. We present a case arising in a 4‐month‐old girl with a giant CMN. She presented for evaluation of a pedunculated lesion at the superior gluteal crease that had been present since birth and exhibited rapid growth. Biopsy of the lesion revealed two distinct components: an expansile proliferation of pleomorphic cells with varying degrees of cellularity and a proliferation of banal‐appearing melanocytic nevic cells. The cells of the expansile proliferation displayed a wide range of morphologic features, including nests of round cells, spindle‐shaped cells, and more differentiated rhabdomyoblasts within a myxoid, highly vascularized stroma. Cross‐striations, a marker of skeletal muscle differentiation, were present. These tumor cells were strongly immunoreactive with desmin, myo‐D1, and myogenin. Fluorescence in situ hybridization analysis with PAX3/7‐FKHR probes was negative. A diagnosis of embryonal rhabdomyosarcoma in association with CMN was made. Initial excision revealed tumor at the margins, and the patient underwent reexcision with subsequent chemotherapy with vincristine, actinomycin D, and cyclophosphamide. She was disease‐free at the 6‐year follow‐up. It has been postulated that the combination of melanocytic and rhabdomyoblastic cells within the same lesion may imply derivation from a common pluripotent stem cell or neural crest cell. Clinicians following patients with giant CMN should consider rhabdomyosarcoma in the differential diagnosis of lesions arising within the nevus.